THE EFFECT OF CREATIVITY AND SKILLS ON BUSINESS SUCCESS IN SMALL AND MEDIUM BUSINESS IN EAST JAKARTA - Amalia, Ira; Sudiarditha, I Ketut R.; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine whether creativity and skills have an influence on business success. The basis of this research is because creativity and skills have a direct relationship with business success. The method used in this research is a survey method. The data used in this study is quantitative data using path analysis . The population in this study is Small and Medium Enterprises (UKM) located in East Jakarta with an affordable population in Cakung District. This sampling used simple random sampling . The sample in this study amounted to 93 entrepreneurs respondents in SMEs located in East Jakarta. The results of this study are: (1) There is a positive and significant effect of Creativity on Skills. (2) There is a positive and significant effect of Creativity on Business Success. (3) There is a skill that has a positive and significant effect on business success. (4) There is a simultaneous positive and significant influence on Creativity and Skills on Business Success.